Progresifitas Regulasi Keuangan Syariah Di Indonesia - Ulum, Fahrur (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2017)
Abstract: This paper discusses about the progressive regulation of Islamic finance in Indonesia and its relation with the governments political will in shariâah financial institutions. The progress of shariâah financial regulation in Indonesia is good enough to solve various demands of operational optimization of shariâah financial institutions in Indonesia. It shows that shariâah financial regulation is massive and experiencing good progressive to answer operational problems of shariâah financial institutions. The situation is also reinforced by the massive of the fatwa of the National Shariâah Council (DSN). Various development programs of Islamic financial institutions conducted by the government through Bank Indonesia, BAPEPPAM, Financial Services Authority (OJK), and DSN show the existence of political will of the government to shariâah financial institutions. To give a certain regulation in order to optimize the operational of shariâah financial institutions, the government has massively issued various regulations. The progressiveness of shariâah financial regulations prove that the political will of the government is seen in the effort of developing syariâah financial institutions. Keywords: Progressivity, regulation, syariâah financial institutions Abstrak: Tulisan ini membahas tentang progresifitas regulasi keuangan syariah di Indonesia dan kaitannya dengan political will pemerintah pada lembaga keuangan syariah. Progres regulasi keuangan syariah di Indonesia cukup bagus untuk menyelesaikan berbagai tuntutan optimalisasi operasional lembaga keuangan syariah di Indonesia. Hal itu menunjukkan bahwa regulasi keuangan syariah cukup masif dan mengalami progresifitas yang baik untuk menjawab persoalan-persoalan operasional lembaga keuangan syariah. Keadaan tersebut diperkuat dengan progres fatwa Dewan Syariah nasional (DSN) yang cukup masif pula. Berbagai program pengembangan lembaga keuangan syariah yang dilakukan oleh pemerintah melalui Bank Indonesia, BAPEPPAM, Otoritas Jasa Keuangan (OJK), dan DSN menunjukkan adanya political will pemerintah terhadap lembaga keuangan syariah. Untuk menjawab kepastian regulasi demi optimalisasi operasional lembaga keuangan syariah, pemerintah secara masif mengeluarkan berbagai regulasi keuangan syariah. Progresifitas regulasi keuangan syariah menjadi bukti bahwa political will pemerintah tampak dalam upaya pengembangan lembaga keuangan syariah. Kata Kunci: Progresifitas, regulasi, lembaga keuangan syariah